KEABSAHAN PERJANJIAN SUROGASI DI INDONESIA - elisa wibowo; Simon Nahak; I Ketut Widia (Jurnal Hukum Prasada, 2017)
Abstract One branch of science and technology (Science and Technology) are developing rapidly today is reproductive technologies. This is an attempt to overcome the problem of infertility (infertility) in couples of childbearing age. Basically artificial insemination through the Babysitting same womb with IVF, it's just the difference between artificial insemination (sutogasi) with test tube baby technique is a process or way as in the conception stage. The lack of regulations governing this will certainly have implications for legal certainty for the parties, because it could have social and economic situation of different causes one of the parties in a weak position. From the above background there are any issues to be researched is the first How keabsahankontrak surogasi, the latter Is surogasi contract has an impact on people's lives in Indonesia. The method used in this research is the method used is normative, ie a study deductively begins by analyzing the articles of the legislation governing the matter in this study, while the normative mean legal research that aims to acquire knowledge about the relationship between a normative regulations with other regulations and application in practice. Approach to the problem used in this study is the approach law (statute approach), cooperative study, approach to the concept (conceptual approach). Primary legal source used is legislation and secondary legal sources using the research results of the study authors then compared with the source material, namely tertiary law dictionary Indonesian and Foreign Languages, internet, journals, and other litelatur. Secondary data collection techniques, carried out by means of a literature study. The conclusion of this study is the first agreement surogasi illegitimate in the eyes of positive law Indonesisa, because it has no legal protection was legal. Both effects that occur in society is socially children born do not have a clear status in the society in which the surrogate mother, surrogate mothers get a lot of criticism of things to do, as the economic aspects of surrogate mothers undergoing significant change. Keywords: Agreements, subrogation